INCREASING THE ENERGY EFFICIENCY OF COMPRESSOR AND FAN ELECTROMECHANICAL SYSTEMS UNDER VARIABLE TECHNOLOGICAL MODES - Shavazov, A.A.; Ilekerova, I.B.; Turaxanov, Sh.Sh. (Research Focus International Scientific Journal, 2026)
This article examines modern methods for increasing the energy efficiency of electromechanical systems with compressors and fans operating under various technological conditions. The influence of variable load, transient processes, partial load modes, and downtime on the energy characteristics of induction electric drives was analyzed. Special attention is paid to reducing energy losses through the use of frequency-controlled drive, adaptive control algorithms, and intelligent control methods. Modern approaches to dynamic modeling of ventilation systems and control of compressor units to achieve energy efficiency are examined. It has been shown that the use of operating mode optimization systems and adjustable electric drives can reduce energy consumption by 20–40 percent, and sometimes even ensure higher energy savings. Recommendations for increasing the efficiency of electromechanical systems under variable technological conditions have been developed based on the analysis of recent scientific research.